Detection of testosterone administration by increased ratio between serum concentrations of testosterone and 17 alpha-hydroxyprogesterone - Carlstrom, K.; Palonek, E.; Garle, M.; Oftebro, H.; Stanghelle, J.; Bjorkhem, I. (Clinical Chemistry, 1992)
An increased ratio between urinary testosterone (T) and epitestosterone (epiT) has been accepted by the International Olympic Committee as a marker for T doping. However, in a few subjects, we and others have observed constantly above-normal urinary T/epiT ratios that are unlikely to be related to exogenous T administration. To find a better test for T doping, we studied several serum and urinary androgens and androgen precursors, estrogens, and luteinizing hormone (LH) in seven healthy volunteers for 35 days after an intramuscular injection of 250 mg of testosterone enanthate. Among urinary analyses, only the T/epiT ratio was a suitable marker of T doping; of the serum assays, 17 alpha- hydroxyprogesterone (17OHP), T/17OHP ratio, LH, and T/LH ratio were fair to good markers of T doping. The serum T/17OHP ratio was the best marker of those tested, with all seven subjects having above-normal values for this in the first 3 days of the observation period. No other marker showed abnormal values in all subjects at any time. Moreover, the T/17OHP ratio was affected by neither diurnal variation nor physical stress. The value of this marker for T doping was further supported by the finding of normal T/17OHP ratios in a subject with increased urinary T/epiT ratios caused by an abnormally low testicular epiT production, probably related to genetic factors. In: Clinical Chemistry, Vol 38, 1779-1784